2013
DOI: 10.1029/2012ja018167
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic waves and electron anisotropies downstream of supercritical interplanetary shocks

Abstract: [1] We present waveform observations of electromagnetic lower hybrid and whistler waves with f ci ≪ f < f ce downstream of four supercritical interplanetary shocks using the Wind search coil magnetometer. The whistler waves were observed to have a weak positive correlation between dB and normalized heat flux magnitude and an inverse correlation with T eh /T ec . All were observed simultaneous with electron distributions satisfying the whistler heat flux instability threshold and most with T ⊥ h /T k h > 1.01. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 65 publications
9
102
0
Order By: Relevance
“…3. A comparison of the THEMIS observations with those from previous Wind and STEREO studies [e.g., Breneman et al, 2013;Wilson et al, 2007Wilson et al, , 2009Wilson et al, 2012Wilson et al, , 2013a show the following: (i) similar modes and comparable electric field amplitudes; (ii) large amplitude ( E ≥ 100 mV/m) high-frequency waves are ubiquitous throughout the entire bow shock transition region and the magnetosheath; and (iii) both magnetosonic-whistler and high-frequency waves are observed regardless of whether the shock was quasi-parallel or quasi-perpendicular. 4.…”
Section: 1002/2014ja019930mentioning
confidence: 99%
See 4 more Smart Citations
“…3. A comparison of the THEMIS observations with those from previous Wind and STEREO studies [e.g., Breneman et al, 2013;Wilson et al, 2007Wilson et al, , 2009Wilson et al, 2012Wilson et al, , 2013a show the following: (i) similar modes and comparable electric field amplitudes; (ii) large amplitude ( E ≥ 100 mV/m) high-frequency waves are ubiquitous throughout the entire bow shock transition region and the magnetosheath; and (iii) both magnetosonic-whistler and high-frequency waves are observed regardless of whether the shock was quasi-parallel or quasi-perpendicular. 4.…”
Section: 1002/2014ja019930mentioning
confidence: 99%
“…Using methods applied in previous studies [e.g., Wilson et al, 2009Wilson et al, , 2012Wilson et al, , 2013aWilson et al, , 2013b, we identified these fluctuations as magnetosonic-whistler waves (details not shown). These waves were observed in every bow shock crossing examined herein.…”
Section: Example Bow Shock Crossingmentioning
confidence: 99%
See 3 more Smart Citations